Pengaruh Rasio Keuangan Terhadap Harga Saham Perusahaan Sektor Teknologi Di Bei - Dayanti, Komang Ayu Trisna; Primasatya, Rieswandha Dio; Hendri Arya Fernando (Owner : Riset dan Jurnal Akuntansi, 2024)
One of the objectives of financial management is to maximize the value of the company. For companies that are already listed on the stock exchange, this objective can be achieved by maximizing the value of the relevant market price. The purpose of conducting existing research is to test empirically the effect of the Debt to Equity Ratio (DER), Current Ratio (CR), Return on Equity (ROE), Net Profit Margin (NPM), and Total Asset Turnover (TATO) on stock prices of technology sector companies listed on the list on the Indonesia Stock Exchange. The research data includes financial data for the 2018-2021 period. The estimation method used is panel data regression. The results of the study provide empirical evidence that Total Asset Turnover (TATO) has a significant effect on the stock prices of technology sector companies listed on the IDX for the 2018-2021 period. Other variables, namely CR, DER, ROE, and NPM have no effect on stock prices.